Konstrukcijski materiali in tehnike spajanja - Rihar, Gabriel (Kovine zlitine tehnologije, 1997)
In order to reduce the own weight of supporting structures and to make the best use of the materials applied, new materials are searched which should have mechanical properties as good as possible and would still permit the making of reliable and dureble joints. Steel is characterized by high bearing strength and low price, and will remain the most important structural material also in future. Welded joints, due to their strength, surpass all other methods of permanent joining; therefore, only the materials permitting high-strength joints making use of the good properties of the parent metal will be taken into consideration in engineering design. One should be aware that with the development of new materials, welding will have less chances left. Local heating to a high temperature and high cooling rates, the result of which is an unfavourable structure in the welded joint, can namely never be avoided.
Keywords: spajanje; varjenje; zvarni spoji; mehanske lastnosti; konstrukcijski materiali